Respuesta :
Answer:
A
Step-by-step explanation:
4x - 5x + 2 = 3(2x - 4)
-x + 2 = 6x - 12
+x +x
2 = 7x - 12
+12 +12
14 = 7x
/7 /7
2 = x
Answer:
A. 2
Step-by-step explanation:
To find the value of x, first, you have to isolate it on one side of the equation. Isolate x on one side of the equation.
4x-5x+2=3(2x-4)
4x-5x=-x (Combine like terms and group like terms.)
-x+2=3(2x-4)
3(2x-4) (Expand.)
DISTRIBUTIVE PROPERTY:
A(B+C)=AB+AC
A(B-C)=AB-AC
3*2x=6x
3*4=12
6x-12
-x+2=6x-12
-x+2-2=6x-12-2 (Subtract 2 from both sides.)
12-2 (Solve.)
12+2=14
-x=6x-14
-x-6x=6x-14-6x (Subtract 6x from both sides.)
-x-6x (Solve.)
-x-6x=-7x
-7x=-14
-7x/-7=-14/-7 (Then, divide by -7 from both sides.)
-14/-7 (Solve.)
-14/-7=2
x=2
Hence, the correct answer is (A.) 2.